G-control Charts for Contamination Rates of Blood Cultures in a University Hospital - Sangsuwan, Tharntip; Darayon, Rungtip; Jamulitrat, Silom (Siriraj Medical Journal, 2021)
Objective: To determine blood culture contamination rates, and display with a g-chart. Materials and Methods: The medical records of patients, from whom blood cultures were obtained in a university hospital, during January and December 2019 were retrieved and reviewed for contamination. The Center for Disease Control and Prevention (CDC) criteria were used to classify the blood culture results. The contamination rates were illustrated with a g-chart. Results: We identified 331 false-positive blood cultures, among 32,961 cultured specimens; yielding a contamination rate of 1.0% (95%CI = 0.9% – 1.1%). The highest contamination events occurred in the Emergency department (49.2%), Pediatric ICU (5.2%) and Neonatal ICU (4.8%), respectively. The most common commensal bacterial genus were Staphylococcus coagulase negative (67.1%), Bacillus spp. (10.2%) and Corynebacterium spp. (7.6%), correspondingly. The g-charts could identify 14 abnormal variations, in 41 locations. Conclusion: The contamination rates found were within ranges of other reports. G-charts are simple to construct, easy to interpret and sensitive for detection of real time epidemics.